Skopos translator theory, text-type and the African postcolonial text in intercultural postcolonial communication (2016)
The postcolonial text is a political and ideological text that is differentiable in translation. This is because of its location in the dialogic and discursive communicative exchange between former colonizer and formal colonized cultures and societies. This communitive exchange takes place in the situation and condition of asymmetrical relations and relations of inequality and involve the contestation of histories, cultures, meaning, identities and representation. The functionally of the postcolonial text with its message IS fixated on this dialogue and discourse; and each postcolonial text is a single statement directly and specifically responding to this dialogue and discourse in some ways. This paper examines the African postcolonial text and its communicative location in the of postcolonial theory and possibilities offers by the skopos functional theory in translation to set aside the purpose and function on the source text intended by the author. Using Chinua Achebe’s text, it would conclude that the mediator role of the translator in the dialogic and discursive exchange between former colorizer and former colonized cultured and societies need not become interference in the applications of the skopos theory.